2013
DOI: 10.1001/jamaoto.2013.1049
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Venous Thromboembolism in Otolaryngology–Head and Neck Surgery

Abstract: The incidence of deep venous thrombosis and pulmonary embolism among the OTO-HNS patient population at our academic center is lower than the incidence reported in previous studies (range, 0.1%-0.3%) and is significantly lower than the incidence observed in other surgical specialties. It is likely that patient- and specialty-specific factors as well as the more aggressive use of venous thromboembolism prophylaxis during recent years are at least partially responsible for the decreased incidence in our populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 14 publications
3
47
0
2
Order By: Relevance
“…Risk of venous thrombosis (0.05%-0.3%) and pulmonary embolism (0.035%-0.2%) following otolaryngological surgery is among the lowest of any surgical subspecialty, with most instances occurring during hospitalizations following major oncologic surgery. [22][23][24] However, to date studies of thromboembolic risk in otolaryngology have focused on a general population and not on hypercoagulable patients with known increased risk of consequential thrombosis. Exemplary studies from other fields provide perspective on associated morbidity and mortality.…”
Section: Perspective On Thrombosis Riskmentioning
confidence: 99%
“…Risk of venous thrombosis (0.05%-0.3%) and pulmonary embolism (0.035%-0.2%) following otolaryngological surgery is among the lowest of any surgical subspecialty, with most instances occurring during hospitalizations following major oncologic surgery. [22][23][24] However, to date studies of thromboembolic risk in otolaryngology have focused on a general population and not on hypercoagulable patients with known increased risk of consequential thrombosis. Exemplary studies from other fields provide perspective on associated morbidity and mortality.…”
Section: Perspective On Thrombosis Riskmentioning
confidence: 99%
“…In otolaryngology, the adoption of routine use of prophylactic anticoagulant medications is less pronounced mainly because of the low risk of VTE in general and the potentially more harmful side effect of chemoprophylaxis that can result in bleeding or hematoma of or around the aerodigestive tract . Garritano et al reported that 7 of 11 surgical services were more likely than the otolaryngology service to provide patients with the institutionally recommended VTE prophylaxis . In another study by Garritano et al that surveyed otolaryngologists, they reported a considerable variability among otolaryngologists in using intraoperative and postoperative thromboprophylaxis, they also reported 88.3% of otolaryngologists stated they would find thromboprophylaxis guidelines released by the American Academy of Otolaryngology ‐ Head and Neck Surgery to be helpful .…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate variability in the importance otolaryngologists place on the risk factors for VTE in their patients. Interestingly, although the utility of preoperative screening remains poorly defined, particularly within the otolaryngology population where the incidence of VTE has already been found to be quite low, a small subset of our respondents (14.9%) reported the use of routine screening for VTE in otherwise asymptomatic patients. A little over half of these respondents (51.9%) were screened for VTE preoperatively and the remainders were screened during the postoperative period.…”
Section: Discussionmentioning
confidence: 84%
“…The most common reason stated by the respondents in this study for not adhering to institutional VTE prophylaxis guidelines is low patient risk for development of VTE (69.1% of respondents). Recent reports in the literature suggest that the incidence of VTE in the otolaryngology patient population is fairly low, with 1 study reporting the VTE incidence to be as low as 0.07% . This low incidence of VTE may also be part of the reason that the use of pharmacologic prophylaxis, with its inherent bleeding risk, has not been routinely adopted by otolaryngologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation